Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian di Toko Oleh - Oleh Rahayu Wates Kediri - Nur Rezza Fadilla; Baju Pramutoko; Ririn Wahyu Arida (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study investigates the influence of the marketing mix on consumer purchasing decisions at Rahayu Souvenir Shop. A quantitative research approach was applied to examine the relationship between the marketing mix elements and consumer behavior. Data collection involved the use of structured questionnaires distributed to consumers. The sample consisted of 95 respondents, selected using the Slovin formula based on the total population of the shop’s customers. Several statistical tests were conducted to ensure data validity and reliability, including validity and reliability tests, as well as classical assumption tests such as normality, heteroscedasticity, and multicollinearity tests. These tests were prerequisites for conducting multiple linear regression analysis. The results of the analysis revealed that the product variable (X1) does not have a significant influence on consumer purchasing decisions, as indicated by a significance value of 0.625 (> 0.05). On the other hand, the price variable (X2) showed a significant influence with a significance value of 0.020 (< 0.05), while promotion (X3) and location (X4) also had significant effects with significance values of 0.009 and 0.000, respectively. Furthermore, the F-test results indicated that the product, price, promotion, and location variables together have a significant effect on purchasing decisions, as shown by a significance value of 0.001 (< 0.05).